PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PERSETUBUHAN KEPADA ANAK (PUTUSAN NOMOR 2/PID.SUS-ANAK/2021/PN.SGR): Application of criminal sanctions against perpetrators of sexual intercourse witha children (desicion Number 2/Pid.Sus-Anak/2021/PN.Sgr) - Audric Farell Nolan; Setiyono (Faculty of Law, Universitas Trisakti, 2024)
This research is motivated by criminal acts of decency, especially sexual intercourse with children which are increasingly widespread. The formulation of the problem in this study is whether the imposition of criminal sanctions below the minimum criminal sanction by the panel of judges in Decision Number 2/Pid.Sus-Anak/2021/PN.Sgr is in accordance with the provisions of Article 81 Paragraph (2) of Law Number 35 of 2014 concerning amendments to Law Number 23 of 2001 concerning child protection? and whether the imposition of sanctions by the panel of judges in Decision Number 2/Pid.Sus-Anak/2021/PN.Sgr is in accordance with the objectives of punishment. This research uses a descriptive analytical normative legal research method which is analyzed qualitatively with deductive logic inference. The research found that the judge's decision in the verdict doesn't align with Article 81 Paragraph (1) of the Child Protection Law, which mandates a sentence of at least 5 years and maximum 15 years, and the punishment's purpose focuses on benefits. The conclusion is that this decision leads to unmet legal objectives, causing legal uncertainty and injustice for victims. The punishment for child defendants aligns with a utilitarian perspective.